Personally Differentiated Approach in Dysgraphia Correction of Primary School Children With General Speech Underdevelopment - Alekseeva, E (KnE Life Sciences, 2018)
In the works of famous authors, we can find well-presented mechanisms of writing and the structure of work to eliminate deviances of reading and writing, related to the deficiency of certain operations of writing, or a deviance of the speech system functioning. According to the conception of A. R. Luria about the psychophysiological mechanisms of writing, the authors revealed the linguistic and optical spatial deviances in the structure of dysgraphia, lexical and grammatical, phonetic-phonemic disorders, skills-formation disorder of linguistic analysis and synthesis; they presented the areas and techniques of preventive and corrective work. The question of children’s condition with writing disorder of psychological level of its organization is not fully studied. The corrective work presented in the article is directed to the elimination of deviances in oral and written speech and aimed at the formation of interhemispheric interaction. The profile of functional asymmetry of hemispheres and the type of leading modality in children were taken into account. Methods of neurolinguistics programming in the correctional process were used as means of psychological correction, harmonization of personality, developing attention, memory, thinking and speech, increasing practical literacy in children. Keywords: writing process correction, neurolinguistics programming, neuropsychological approach, written speech motivation, sensory perception, regulation, self-control